PENGARUH MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE TERHADAP PEMBELAJARAN PASSING SEPAK BOLA - Bardiono Bardiono; Andika Triansyah; Uray Gustian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe research problem is whether there is an influence of the cooperative laerning model type of think pair share on learning the basic techniques of passing football. The purpose of this study, "to determine the effect of think pair share cooperative learning models on learning outcomes of basic passing technical skills in soccer learning for students". This study uses an experimental method, using a one group pretest-posttest design research model. The population in this study was grade VII students of SMP Negeri 1 Maya Island, amounting to 60 students where 30 students were class VII A and 30 students were class VII B. Samples from this study were 30 students. The results obtained from the average data increase at pretest 48.83, while at posttest 76.56. From the results of testing the data obtained that t count 8.801 while t table 1.699 at a significance level α = 0.05 with dk (n-1) (30-1) = 29. The test criteria is if t count 8.801 > t table 1.699 then Ho is rejected and Ha accepted. Based on the results of the analysis it can be concluded that answering the research hypothesis that the hypothesis is accepted, it means that there is a significant influence on the cooperative learning model of think pair share type on the basic technical skills of passing football. The percentage increase of 59.80%.Keywords: Cooperative Learning Model, Think Pair Share, Football Passing